THE INFLUENCE OF SERVICE QUALITY ON TAXPAYER SATISFACTION AND TAXPAYER COMPLIANCE AT BAPENDA RIAU PROVINCE - Tengku Arief Lukman; Layla Hafni; Harry Patuan Panjaitan; Teddy Chandra; Sheerad Sahid (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
The study was conducted in BAPENDA of Riau Province. The aim was to determine the direct effect of the Dimensions of Service Quality namely tangibility, empathy, reliability, responsiveness and assurance on the satisfaction of taxpayers and taxpayer compliance. This study gathered a Sample of 145 people using the proportional random sampling technique by distributing a questionnaire. The variables used were Service Quality, taxpayer satisfaction and taxpayer compliance. The data were analyzed using SEM (Structural Equation Modelling) analysis with SmartPLs 4.0. The results showed that there was an effect of service quality on taxpayer satisfaction, service quality had a significant positive effect on taxpayer compliance and there was a relationship between taxpayer satisfaction and taxpayer compliance variables.